Pengabdian Masyarakat Melalui Pemasaran Produk Secara Digital di Desa Wujil Kabupaten Semarang - Hardian Mursito; Meida Rachmawati (Jurnal Nusantara Berbakti, 2024)
This research was carried out with the aim of providing training and assistance on digital marketing of products that are potential in Wujil Village, namely meatball tofu, angkingan, restaurants and the furniture industry. This research uses a qualitative method which results in the conclusion that by digitalizing products in Wujil Village, Semarang Regency, there has been a significant increase in consumers in the meatball tofu, angkingan, restaurant and furniture industry sectors, thereby improving the welfare of the people of Wujil Village.